Pengaruh kualitas produk dan kualitas pelayanan terhadap kepuasan konsumen (studi kasus Nikimi Mart Tebo) - Iliyas, Iliyas; Dahmiri, Dahmiri; Nifita, Ade Titi (Jurnal Dinamika Manajemen, 2021)
The high public interest in shopping has made retail businesses see opportunities to make profits. Not only local retailers, but foreign modern retailers are also making Indonesia their potential target. The entry of foreign retailers will be a threat to local retailers who have previously controlled the market. This study aims to test whether product quality and service quality have an effect on customer satisfaction. The object under study is the consumer at Nikimi Mart Tebo. This research is a quantitative research. The sample used in this study were customers who had shopped at Nikimi Mart. The sampling technique used accidental sampling. Data collection techniques are primary data or data taken directly from respondents through questionnaires. This study uses multiple linear regression and descriptive analysis for data analysis with the help of the SPSS Version 21 program. This study has the results that product quality, service quality simultaneously have a positive effect on customer satisfaction and product quality, service quality, have a partial negative effect on customer satisfaction.